2017
DOI: 10.1111/bpa.12478
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasomes as therapeutic targets for Alzheimer's disease

Abstract: Alzheimer's disease is the most common form of progressive dementia, typified initially by short term memory deficits which develop into a dramatic global cognitive decline. The classical hall marks of Alzheimer's disease include the accumulation of amyloid oligomers and fibrils, and the intracellular formation of neurofibrillary tangles of hyperphosphorylated tau. It is now clear that inflammation also plays a central role in the pathogenesis of the disease through a number of neurotoxic mechanisms. Microglia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
84
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(84 citation statements)
references
References 173 publications
(296 reference statements)
0
84
0
Order By: Relevance
“…One recent study reported a decrease in A20 mRNA levels in the blood of PD patients (Perga et al, ) similar to that reported in chronic inflammatory diseases (Gilli et al, ), supporting the potential use of A20 as a biomarker. During the last decade, the NLRP3 inflammasome has emerged as a promising pharmacological target for the prevention and treatment of a number of immune‐related diseases, including cancer, type II diabetes, rheumatoid arthritis and AD (Çimen et al, 2016; Coll et al, ; Lamkanfi & Dixit, ; White, Lawrence, Brough, & Rivers‐Auty, ). Strategies for controlling inflammasome activity are already being considered in clinical trials for some of these disorders, and might, if successful, be extended to subgroups of PD patients presenting aberrant NLRP3 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study reported a decrease in A20 mRNA levels in the blood of PD patients (Perga et al, ) similar to that reported in chronic inflammatory diseases (Gilli et al, ), supporting the potential use of A20 as a biomarker. During the last decade, the NLRP3 inflammasome has emerged as a promising pharmacological target for the prevention and treatment of a number of immune‐related diseases, including cancer, type II diabetes, rheumatoid arthritis and AD (Çimen et al, 2016; Coll et al, ; Lamkanfi & Dixit, ; White, Lawrence, Brough, & Rivers‐Auty, ). Strategies for controlling inflammasome activity are already being considered in clinical trials for some of these disorders, and might, if successful, be extended to subgroups of PD patients presenting aberrant NLRP3 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…38 Moreover, in vitro experiments suggested an anti-inflammatory effect of AChEI on atherosclerosis. 39 As inflammation is important for AD and dementia, 40 a possible modulatory effect of AChEI on inflammation might result in decreased mortality rates in patients treated with antidementia drugs. Unfortunately, the present study was not powered to explore the different causes of death driven by antidementia drugs, and further studies are needed to address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several advances have been made in the identification of exogenous compounds that may block IL-1 signaling or serve as inhibitors of NLRP3 inflammasome activation (White et al, 2017; see Figure 3); however, most compounds are in the early stages of development.…”
Section: Targeting the Nlrp3 Inflammasome For The Treatment Of Neurolmentioning
confidence: 99%